KONTRIBUSI KOMPETENSI PROFESIONAL GURU PADA RENCANA PELAKSANAAN PEMBELAJARAN PASCAPELATIHAN KURIKULUM 2013 PROVINSI JAWA TENGAH TAHUN 2017 - Mulida Hadrina Harjanti (Universitas Muhammadiyah Semarang, 2018)
The objectives of this study are: 1) to explain that professional competence can contribute to the quality of lesson plans; 2) to show the implementation results of the curriculum 2013 posttraining through the curriculum 2013 supervision program in 2017. The method that is used in this study is a qualitative descriptive method. The results of this study indicate that professional competence can contribute to the preparation of learning plans, while the components of professional competence are: 1) mastering the material, structure, concepts, and scientific mindset that supports the subject matter that is taught; 2) master the competency standards and basic competencies of the subjects / fields of development that is taught; and 3) developing creative learning material. While the implementation results of the curriculum 2013 posttraining through the curriculum 2013 supervision program in 2017 on aspects of the lesson plan are in very good and good category. However, it is still necessary to pay attention and increase the components that are still in the good category so that they can improve very well in the following year. Of the four levels, only the senior high school level received a score of 3.52 with a very good predicate, while the elementary, junior high, and vocational high school levels were still in a good position. Keywords: teacher’s professional competence, posttraining, curriculum2013